2017
DOI: 10.52324/001c.8022
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Occupational Segregation, and the Cultural Divide: Are Red States Different than Blue States?

Abstract: This paper examines geographic differences in occupational segregation by sex in male-dominated, higheducation STEM and non-STEM occupations to determine if labor market conditions for women vary according to red-state/blue-state patterns. Controlling for state demographic variables, economic factors, and labor market characteristics, our results show that there are indeed differences in labor market outcomes along red-state/blue-state lines, with blue states showing more integrated labor market outcomes than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The literature (e.g. Kifle et al, 2014;May and McGarvey, 2017) has shown the existence of a multi-dimensional nature of occupational segregation by sex represented by different statistics (female labour force participation rate, occupational segregation by sex in male-dominated, high-education science, technology, engineering, and math (STEM)and non-STEM occupations, and others). This segregation may be directly related to the level of women's satisfaction in the labour market which influence women's turnover rate.…”
Section: Discussionmentioning
confidence: 99%
“…The literature (e.g. Kifle et al, 2014;May and McGarvey, 2017) has shown the existence of a multi-dimensional nature of occupational segregation by sex represented by different statistics (female labour force participation rate, occupational segregation by sex in male-dominated, high-education science, technology, engineering, and math (STEM)and non-STEM occupations, and others). This segregation may be directly related to the level of women's satisfaction in the labour market which influence women's turnover rate.…”
Section: Discussionmentioning
confidence: 99%
“…Employers in more egalitarian minded communities and with more same‐sex couples, tend to have less inequality (Beggs, 1995; Garnett, 2012; Skaggs, 2008). Greater levels of voting for Democrats is correlated with lower rates of occupational segregation by race and gender (May & McGarvey, 2017; McVeigh & Sobolewski, 2007).…”
Section: Constructionism and Employment Discrminationmentioning
confidence: 99%
“…Although some previous studies have examined the association between geopolitics and public attitude towards immigration policy in the USA, the results are inconsistent and inconclusive (Bessett et al, 2015 ; May & McGarvey, 2017 ; Stanhope et al, 2019 ). Thus, it leads to calls for further investigation to bring nuance and augment the existing findings (Stanhope et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Each of the fifty states in the USA can be viewed or categorized as either red (republican) or blue (democrat) states based on electoral or voting patterns, majority political ideology, and the dominance of either the Republican or Democratic party in the state (Levendusky & Pope, 2011 ; Miller & Conover, 2015 ; Nivola & Brady, 2007 ; Rodden, 2005 ). Some studies refer to this phenomenon as geopolitics—the intersection of politics and geography (Davisson, 2011 ; May & McGarvey, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation